HILIRISASI TEKNOLOGI PENGASAPAN PERIKANAN PADA KELOMPOK PENGOLAH PEMASAR (POKLAHSAR) IKAN SALAI BAROKAH, KARYA JAYA KERTAPATI, PALEMBANG - Selly Ratna Sari; Guttifera Guttifera; Maya Resta Kanya; Dendi Dendi; Reza Mahendra (Jurnal Abdi Insani, 2023)
Poklahsar Ikan Salai Barokah have 11 members. The group of processors of marketers was start in 2014. Currently, Poklahsar (Group of negotiators) is chaired by Mrs. Sri Indrawati who is located at Jalan Mayjen Yusup Singadekane RT 22 RW 05 Keramasan Village, Kertapati District, Palembang. Poklahsar ikan salai barokah in an area that is currently being widened. Priority issues that will be addressed in the com. service program are production management and marketing. The purposed is community service to the Ikan Salai barokah is to carried out community service programs according to national higher education standards, namely lecturers and students can carry out the PKM program, develop a community empowerment model that is in accordance with local conditions, meaning that problems due to road repairs can make alternative smoking tools that are portable and standard, increase the capacity of lecturers' service to the community, Activities carried out include Socialization introduction to smoke fishery processed products in general that are standardized and explain the benefits of gambir introduction, give of investment tools for smoking and coaching regarding business management and marketing management through digital marketing (social media).